THE SERVICE QUALITY OF THE EMPLOYEES AT A FINANCIAL LOAN COMPANY IN BANG PLA ROAD COMMUNITY - Intaraprasit, Surapot; Visitnitikija, Andchinnaso (Journal of MCU Nakhondhat, 2024)
This research aims to 1) Examine the service quality of loan officers at a financial loan company in the Bang Pla community, 2) Assess customer satisfaction with the services provided by the loan officers at the same company, and 3) Compare customer satisfaction across different demographic groups. A sample of 400 respondents was selected for the study, and data were collected using a questionnaire. The data were analyzed using descriptive statistics (percentage and mean), t-tests, F-tests (One-way ANOVA), and Multiple Regression Analysis. The majority of respondents were female, aged between 31 - 40 years, employed in the private sector, with an education level below a bachelor’s degree, and an average monthly income of less than or equal to 20,000 THB. Overall, the service quality and customer satisfaction were rated at the highest level. There was no statistically significant difference in customer satisfaction among different demographic groups at the .05 significance level. The service quality dimensions - tangibility, reliability, responsiveness, assurance, and empathy-significantly influenced customer satisfaction at the .01 significance level.